Spokewise iridotomy combined with Descemet stripping automated endothelial keratoplasty in iridocorneal endothelial syndrome - Zhang, Jiaxin; Peng, Rongmei; Xiao, Gege; Wang, Minshu; Hong, Jing (Frontiers in Medicine, 2023)
Purpose: Iridocorneal endothelial (ICE) syndrome is a progressive anterior segment disorder that can be tricky to treat. Keratoplasty is commonly used to treat corneal edema in ICE syndrome. However, glaucoma is an important risk factor affecting graft survival. To address this question, we designed a retrospective cohort study to evaluate the effect of Spokewise Iridotomy (SI) on Descemet Stripping Automated Endothelial Keratoplasty (DSAEK) Grafts in Iridocorneal Endothelial (ICE) Syndrome. Methods: It was a retrospective cohort study. A total of 29 patients, 31 eyes with ICE syndrome underwent DSAEK at Peking University Third Hospital from June 2015 to June 2022, including 11 eyes with combined SI during DSAEK. The aim was to explore the effect of SI on vision, glaucoma control, complications, peripheral anterior synechiae recurrence, endothelial cell count, and graft survival. Results: The median follow-up time was 30.83months(mo.) in the SI+Endothelial Keratoplasty (EK) group and 6.17mo in the EK group. The 2-year cumulative survival rate of grafts in the SI+EK group was 100%, compared with the 6-month and 1-year cumulative survival rates of 80.2% and 63.2% in the EK group (p=0.043). The SI+EK group had a lower incidence of immediate postoperative complications (p=0.005), fewer postoperative anti-glaucoma medications (AGMs) (p=0.029), smaller peripheral anterior synechiae recurrence(p=0.001), and significant visual acuity improvement (p<0.05). More AGMs were used in failed grafts (p=0.002). Conclusions: SI can help control intraocular pressure, improve visual acuity, and increase graft survival after DSAEK in ICE syndrome patients.